Application of Augmented Reality Media on Short Distance Running Material on the Level of Excitement of Class XI Students at Al-Islam Krian High School - Putri, Intan Amelia; Mochamad Ridwan (Jurnal Pendidikan Jasmani (JPJ), 2023)
Using augmented reality media in the learning process can create excitement. Happiness belongs to positive emotions. Emotions are related to the learning process, the information that enters the students then they remember what the teacher conveys, this is influenced by emotions. In addition, emotions also affect academic achievement. Joy can trigger an overflow of positive emotions that activate the nerves of the brain to record the material being given by the teacher easily because feelings and attitudes will have a very strong influence on the learning process so that a person will have the desire to learn with all his abilities if he likes what is being learned. and he will feel happy to be involved in it. This research method is quantitative with a pre-experimental approach. The research design used the one case study with a purposive sampling technique. the total population is 489 with a sample that will be used as many as 114 students. The results of the study used an excitement questionnaire with 23 questions covering several aspects. Positive aspects of 18.21%, Aspects of full involvement of 18.42%, Aspects of establishing positive relationships with teachers and friends of 24.60%, Aspects of finding meaning in everyday life 12.86%, Achievement aspects of 12, 81%, and external factor aspects of 13.10%. The learning process uses augmented reality media to be used as teaching aids which will be presented in 3D visual form virtually (virtual) which are packaged in the form of modules as learning media or creative and innovative demonstration tools so that they can increase the enthusiasm of students in learning short-distance running material. in PJOK learning.